Political fragmentation, fiscal policy and economic growth in Indian States - Yogesh Uppal; Thushyanthan Baskaran (The European Journal of Comparative Economics)
We study how a fragmented political landscape affects fiscal policy and economic growth with a sample of 15 Indian States over the period 1980-2000. We measure state-level political fragmentation with an inverse Herfindahl index for party vote shares in the state legislature. Our results show that political fragmentation distorts fiscal policy: it entails higher spending, lower revenues, and higher public debt. At the disaggregated level, political fragmentation leads to higher current and lower capital expenditures. These fiscal distortions, in turn, lower growth rates. We also find that informational issues play an important role in determining the effect of political fragmentation.